Investigation of new seed mixtures in wildlife forage ground managem - Antal, Borbála; Szendrei, László; Rédei, Károly; Csajbók, József (Acta Agraria Debreceniensis, 2013)
One of the most important method of habitat development is wildlife forage ground management. Many plant species can be grown on the crop fields, as mixture, too. Use of seed mixtures has not been spread on the native wildlife forage ground, however there are many advantages of them. The aim of the research is to examine the role of the different plant species, seed mixtures in the game feeding, the savouriness of the plants of crop fields, as well as ascertain which seed mixtures are more suitable for wildlife forage ground management. On the basis of the investigation it can be find out that big amount of forage can be produced on mixed crop fields. Buckwheat, corn, rape, millet and white lupine proved to be the most beloved plants. It is suitable to make such mixed forages and use widely in the native wildlife forage ground management, – which assures better feed conditions for the game, – which are more attractive for the game and can draw away from other areas, so prevent, reduce game damage in forestry sector and in agriculture that is in the forest manager’s, agricultural and game manager’s interests, too.